The Doctor and the Elderly (Res Medica, 2014)
Specialism in medicine is an inevitable accompaniment of modern life and one of the newest specialties is Geriatrics (or as many of us would prefer — geriatric medicine). Medical specialties develop for a variety of reasons, for example, the specialty of renal diseases has grown out of the great technical advances in diagnosis and treatment in recent years. Other specialties have developed more gradually as the total body of relevant knowledge has accumulated, for example, cardiology and neurology. Other specialties have appeared as a direct response to the needs of the community, and this is the category into which we place geriatric medicine. With the increasing numbers of old people consequent upon the much higher proportion who survive to old age, the needs of the elderly have escalated and it has been necessary to attempt to deal with this crisis in different and sometimes novel ways. At the same time as numbers of old people have been increasing, many of the traditional family patterns of care have been eroded by social alterations, and so we have both demographic and social reasons for a "geriatric crisis” . It is commonplace now to find that the married daughter (in her 30’s or 40’s) is unable to afford her mother more than token support because she herself is in paid employment and only available for housewifely and family tasks in the evening.The result has been a great increase in declared demand for services for the elderly. Nor is this the whole story, because many studies in different areas of the Western World have shown that old people's needs are often unknown until a crisis occurs (a fall, an acute infection, a stroke, or sometimes simply illness of a custodial relative or neighbour) and the situation is then found to be very advanced and perhaps irreversible and preventable sequelae have occurred.